2015
DOI: 10.4103/0973-029x.164530
|View full text |Cite
|
Sign up to set email alerts
|

Palatal changes of reverse smokers in a rural coastal Andhra population with review of literature

Abstract: Aim:To investigate and record the palatal changes in individuals habituated to reverse chutta smoking in rural coastal Andhra population.Materials and Methods:Sixty individuals out of whom 47 females and 13 males habituated to reverse smoking with no other tobacco and alcohol habits and no other systemic disturbances were selected. The palatal changes were recorded by six examiners. Database were searched for the following terms “reverse smokers,” “nicotina palatini” and “palatal lesions.”Results:The mean and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Ramesh et al also reported a significant decrease in cell size and a substantial increase in nuclear size from healthy cells to mucosal lesions with dysplasia and further dysplasia to squamous cell carcinoma [35]. Lavanya et al reported similar findings from standard samples to lesions with a white patch and further from red areas to squamous cell carcinoma in reverse smokers [36].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Ramesh et al also reported a significant decrease in cell size and a substantial increase in nuclear size from healthy cells to mucosal lesions with dysplasia and further dysplasia to squamous cell carcinoma [35]. Lavanya et al reported similar findings from standard samples to lesions with a white patch and further from red areas to squamous cell carcinoma in reverse smokers [36].…”
Section: Discussionmentioning
confidence: 83%
“…The reduction in cellular diameter and increase in nuclear diameter can be an early indication of malignant changes, and this reflects the dysplastic changes taken place in premalignant lesions as compared to the normal oral mucosa. So, the premalignant lesions can be considered an intermediate stage in the range from normal to carcinoma [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their criteria included the disorder affecting more than two different oral sites and the existence of a verrucous area. Initial clinical presentation could be flat white lesions (without any verrucous component) (Batsakis et al, 1999;Villa et al, 2018) and initially may also sometimes have a lichenoid clinical appearance (Garcia-Pola et al, 2016;McParland & Warnakulasuriya, 2020) and be signed out as being lichenoid by the pathologist. In the latter situation, it is possible that a case could be erroneously treated as OLP for many years, with the risk of missing, or of accelerating, subsequent malignancy.…”
Section: Proliferative Verrucous Leukoplakiamentioning
confidence: 99%
“…The oral mucosal lesions predominantly associated with reverse smoking are hyperpigmentation, depigmentation, stomatitis nicotina, preleukoplakia, leukoplakia, erythroplakia, and palatal cancer. [489] Despite its harmful effects on health, hardly any literature exists pertaining to the social and psychological factors associated with its initiation and abiding factors of reverse smoking. Hence, in the current study, a qualitative research was conducted to comprehend the various psychological and social factors associated with reverse smoking.…”
Section: Discussionmentioning
confidence: 99%